Why fintechs cooperate with banks: Evidence from Germany - Max Bömer; Hannes Maxin (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
We developed a conceptual framework to explain why young financial technology companies (fintechs) seek to cooperate with incumbents from the finance sector. Examining 14 case studies on fintech-bank cooperation, we identified three main reasons: first, banks enable a fintech's market entry; second, banks increase a fintech's profits; and finally, banks enable new fintech products. We observed that each of these reasons is related to particular resources, which fintechs obtain through their cooperation partner. Additionally, we found that fintechs use different label approaches to sell their products when they cooperate with banks. Based on these results, we developed propositions that can be tested in future research.
Keywords: G21; M13; 330; Fintechs; Banks; Cooperation; Regulation; Reputation; Label